An electrical impedance monitoring method of water-lubricated oil transportation. (December 2015) - Kwon, Hyeuknam; Choi, Jung-Il; Seo, Jin Keun
Abstract: We propose a simple and efficient monitoring system based on a single-drive interleaved electrode impedance technique that provides cross-sectional images for real-time detection of fouling in oil–water flows. The simple monitoring method is proposed using a data-interface formula relating between voltage differences measured at sensing electrodes and interfaces of the two immiscible fluids in a pipeline. We estimate the minimum distance between the interface and pipe wall at the images, that is an indicator for monitoring the fouling, by using a voltage–distance map. The robustness of the proposed method is validated through various numerical simulations including oil–water flows in an U-bend return pipe. Abstract : Highlights: We propose a simple and efficient monitoring EIT system for real-time detection of fouling in oil–water flows. We develop a data-interface formula relating between voltage differences and the interfaces We estimate the minimum distance from the interface to the pipe wall for monitoring the fouling by using a voltage–distance map. The robustness of the proposed method is validated through various numerical simulations.